2015
DOI: 10.7863/ultra.15.14.08016
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal Lung Sonography

Abstract: In neonates with early respiratory distress, lung sonography has high interobserver agreement even between interpreters with varying levels of experience.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(19 citation statements)
references
References 24 publications
1
16
0
Order By: Relevance
“…The high level of agreement between LUS and CXR, even in operators with different levels of training, suggests that LUS could be used in routine clinical practice to overcome the main limitation of previous studies in which LUS was performed by a single experienced sonographer. On the other hand, our findings are consistent with those of Brusa et al [22], who previously demonstrated that LUS has high interobserver agreement, even between sonographers with different levels of experience.…”
Section: Discussionsupporting
confidence: 83%
“…The high level of agreement between LUS and CXR, even in operators with different levels of training, suggests that LUS could be used in routine clinical practice to overcome the main limitation of previous studies in which LUS was performed by a single experienced sonographer. On the other hand, our findings are consistent with those of Brusa et al [22], who previously demonstrated that LUS has high interobserver agreement, even between sonographers with different levels of experience.…”
Section: Discussionsupporting
confidence: 83%
“…The neonatologists involved in the study were trained in LUS technique and data could be worse for novice. However, it was demonstrated that LUS learning curve is quite short [ 14 ] and even beginner operators had high reliability in neonatal diagnosis when compared with experienced one [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…Gomond-Le Goff et al [ 32 ] achieved good inter-rater agreement results independent of the raters' experience by retrospectively rating still images of LUS that had been performed in critically ill neonates. In another study similar to ours, four raters with different levels of experience retrospectively interpreted videoclips taken from 114 neonates with respiratory distress, and the physicians with different levels of experience were able to achieve good interobserver agreement [ 33 ]. Gullett et al [ 34 ] evaluated the agreement among emergency physicians with different levels of experience with regard to findings in different lung zones.…”
Section: Discussionmentioning
confidence: 97%